Sorption of benzo(a)pyrene and of a complex mixture of petrogenic polycyclic aromatic hydrocarbons onto polystyrene microplastics - Martínez-Álvarez, Ignacio; Le Menach, Karyn; Devier, Marie-Hélène; Cajaraville, Miren P.; Orbea, Amaia; Budzinski, Hélène (Frontiers in Environmental Chemistry, 2022)
Microplastics (MPs) largely occur in aquatic ecosystems due to degradation of larger plastics or release from MP-containing products. Due to the hydrophobic nature and large specific surface of MPs, other contaminants, such as polycyclic aromatic hydrocarbons (PAHs), can potentially sorb onto MPs. Several studies have addressed the potential impact of MPs as vectors of PAHs for aquatic organisms. Therefore the role of MPs as sorbents of these compounds should be carefully investigated. The present study aimed to determine the sorption capacity of benzo(a)pyrene (B(a)P), as a model pyrolytic PAH, to polystyrene (PS) MPs of different sizes (4.5 and 0.5 μm). In addition, the sorption of PAHs present in the water accommodated fraction (WAF) of a naphthenic North Sea crude oil to 4.5 μm MPs was also studied as a model of a complex mixture of petrogenic PAHs that could appear in oil-polluted environments. The results indicated that 0.5 μm MPs showed higher maximum sorption capacity (Qmax) for B(a)P (145–242.89 μg/g) than 4.5 μm MPs (30.50–67.65 μg/g). From the WAF mixture, naphthalene was sorbed at a higher extent than the other PAHs to 4.5 μm MPs but with weak binding interactions (Kf = 69.25 L/g; 1/n = 0.46) according to the analysis of the aqueous phase, whereas phenanthrene showed stronger binding interactions (Kf = 0.24 L/g; 1/n = 0.98) based on the analysis of the solid phase. Sorption of PAHs of the complex WAF mixture to 4.5 μm MPs was relatively limited and driven by the hydrophobicity and initial concentration of each PAH. Overall, the results indicate that sorption estimations based solely on the analysis of the aqueous phase could overestimate the capacity of MPs to carry PAHs. Therefore, controlled laboratory assays assessing the “Trojan Horse effect” of MPs for aquatic organisms should consider these findings in order to design accurate and relevant experimental procedures.